2021
DOI: 10.3390/genes12020159
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated Immune Pathway Associated with Palbociclib Resistance in Preclinical Breast Cancer Models: Integrative Genomics and Transcriptomics

Abstract: Recently, cyclin-dependent kinase (CDK) 4/6 inhibitors have been widely used to treat advanced hormone receptor-positive breast cancer. Despite promising clinical outcomes, almost all patients eventually acquire resistance to CDK4/6 inhibitors. Here, we screened genes associated with palbociclib resistance through genomics and transcriptomics in preclinical breast cancer models. Palbociclib-resistant cells were generated by exposing hormone receptor-positive breast cancer cell lines to palbociclib. Whole-exome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Furthermore, overlapping myelosuppression (e.g., neutropenia) is another concern when two myelosuppressing agents are combined. Some preclinical studies previously demonstrated the antagonism between CDK4/6 inhibitors and chemotherapeutic agents, where CDK4/6 inhibitors protected the cells from chemotherapeutic agents because both drugs were given simultaneously [ 35 , 36 ]. However, the sequential treatment of CDK4/6 inhibitor and chemotherapy synergistically potentiated the combination efficacy in other preclinical studies [ 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, overlapping myelosuppression (e.g., neutropenia) is another concern when two myelosuppressing agents are combined. Some preclinical studies previously demonstrated the antagonism between CDK4/6 inhibitors and chemotherapeutic agents, where CDK4/6 inhibitors protected the cells from chemotherapeutic agents because both drugs were given simultaneously [ 35 , 36 ]. However, the sequential treatment of CDK4/6 inhibitor and chemotherapy synergistically potentiated the combination efficacy in other preclinical studies [ 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…inhibitor and so on. The increased expression of CDK6 may be due to the deletion of the FAT1 gene (19, 34), and CDK2 overexpression may be due to the activation of the CCNE-CDK2 pathway (35,36). The causes of PI3K/AKT/mTOR pathway activation are a hot topic of research, including PTEN loss of function, AKT1 alteration, PI3K mutation, etc (37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Cell-dependent kinase (CDK) is involved in many tumors related biological processes, such as cell cycle, immune checkpoint ( Hume et al, 2020 ), RNA transcription ( Al-Sanea et al, 2021 ), cell proliferation ( Liu J. et al, 2021 ). Recently, there have been studies on CDK4 ( Pandey et al, 2021 ) and CDK6 ( Pandey et al, 2021 ), but the mechanism of CDK2 ( El-Sattar et al, 2021 ) in cancer is relatively lacking. In our study, we deeply studied CDK2 and constructed the related immune prediction model.…”
Section: Discussionmentioning
confidence: 99%